Antibiotic Resistance in Selected Emerging Bacterial Foodborne Pathogens-An Issue of Concern? - Katarzyna Grudlewska-Buda; Justyna Bauza-Kaszewska; Natalia Wiktorczyk-Kapischke; Anna Budzyńska; Eugenia Gospodarek-Komkowska; Krzysztof Skowron (MDPI AG, 2023)
Antibiotic resistance (AR) and multidrug resistance (MDR) have been confirmed for all major foodborne pathogens: Campylobacter spp., Salmonella spp., Escherichia coli and Listeria monocytogenes. Of great concern to scientists and physicians are also reports of antibiotic-resistant emerging food pathogens-microorganisms that have not previously been linked to food contamination or were considered epidemiologically insignificant. Since the properties of foodborne pathogens are not always sufficiently recognized, the consequences of the infections are often not easily predictable, and the control of their activity is difficult. The bacteria most commonly identified as emerging foodborne pathogens include Aliarcobacter spp., Aeromonas spp., Cronobacter spp., Vibrio spp., Clostridioides difficile, Escherichia coli, Mycobacterium paratuberculosis, Salmonella enterica, Streptocccus suis, Campylobacter jejuni, Helicobacter pylori, Listeria monocytogenes and Yersinia enterocolitica. The results of our analysis confirm antibiotic resistance and multidrug resistance among the mentioned species. Among the antibiotics whose effectiveness is steadily declining due to expanding resistance among bacteria isolated from food are β-lactams, sulfonamides, tetracyclines and fluoroquinolones. Continuous and thorough monitoring of strains isolated from food is necessary to characterize the existing mechanisms of resistance. In our opinion, this review shows the scale of the problem of microbes related to health, which should not be underestimated.